Підготовка вихователів дошкільних закладів до інтерактивного навчання і виховання дітей дошкільного віку - Маріанна Островська; Osztrovszka Marianna (Видавництво «Код», 2025)
Резюме. У статті авторкою розглянуто та досліджено володіння інтерактивними технологіями та вміння використовувати комп’ютерні засоби для вирішення різноманітних завдань у сучасному суспільстві. Навчання технології створення інтерактивних дидактичних ігор є складним процесом.

Abstract. In the article, the author considers and studies the mastery of interactive technologies and the ability to use computer tools to solve various problems in modern society. Learning to create interactive didactic games is a complex process. Teachers who use interactive whiteboards in their work first learn to use them as ordinary projection screens on which a computer displays images. Firstly, interactive technologies in the classroom significantly accelerate the transfer of knowledge and provide technological and social experience not only between generations, but also between individuals. The systematic introduction of interactive technologies in modern education is becoming a key factor in shaping the educational system, meeting the requirements of the information society and the process of reforming traditional approaches. The main goal of using interactive technologies is to create a single information educational space in which all participants of the educational process – administration, teachers, students and their parents - will be interconnected at the information level. Interactive forms of learning for teachers contribute to their activation, bring new ideas and fresh thoughts into the educational process, help to unite the team and have significant advantages compared to traditional forms of activity. Interest in them arises due to their originality and novelty. The use of game methods helps to remove barriers in communication, such as the fear of making a mistake or making the wrong decision. These methods reveal the potential of the individual, including his competence, independence, decision-making skills and ability to interact. The development of a child occurs through various types of activities, and it is especially clearly manifested in group classes in specially equipped centers under the guidance of a teacher. This activity should be active and energetic. That is why interactive methods are effective and necessary for working with preschool children.
Training of preschool teachers for interactive teaching and upbringing of preschool children
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-14
Keywords: майбутні вихователі; дошкільнята; інтерактивні технології; підготовка